The complete chloroplast genome sequence of Asplenium komarovii Akasawa, a rare fern in South Korea - Namjoo Heo; Seona Yun; Danilo D. Fernando (Mitochondrial DNA. Part B. Resources, 2021)
We sequenced the complete chloroplast genome of Asplenium komarovii Akasawa (syn: Asplenium scolopendrium L. subsp. japonicum (Komarov) Rasbach, Reichstein & Viane), which is designated as a rare species in South Korea. The complete chloroplast genome is 149,393 bp in total length and comprised of the following regions: large single copy (82,464 bp), small single copy (21,345 bp), and a pair of inverted repeats (22,792 bp). The overall GC content is 40.9% and the genome encoded a total of 115 genes, including 84 protein-coding, 27 transfer RNA, and 4 ribosomal RNA genes. Phylogenetic analysis based on 21 representative chloroplast genomes of the suborder Aspleniineae (and one outgroup) indicates that Aspleniaceae is monophyletic and sister to Diplaziopsidaceae, with Rhadidosoraceae as the basal group in this three family clade. Asplenium komarovii is sister to A. nidus and A. prolongatum with strong bootstrap support. The chloroplast genome of A. komarovii will be useful in establishing its relationships within the A. scolopendrium complex, which is currently unresolved.